[No more Sabado nights] - Coronel, Shiela; Magsanoc, Kara; Rimban, Luz (The Center, 1996)
Tells the story of how the women of Tawid Sapa, a slum in Novaliches, organized themselves against wife-beating, set up refuge for battered women, and even got the government to install electric lines and deep wells in their community.